Family matters: endogenous gender discrimination in economic development - Fazeer Rahim; José Tavares (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We present a growth model where savings, fertility, labour force participation and gender wage discrimination are endogenously determined. Households consist of husband and wife, who disagree on how to allocate resources to their individual consumption. Household decisions are made by bargaining and the bargaining power of each spouse depends on the market income he/she brings home. This provides the basis for the reluctance of men to grant women equal access to labour markets despite the fact that this hurts them in terms of reduced family income. Economic development makes discrimination costlier, initiating a positive cycle of high female participation, low fertility and high growth. Our empirical study is in two parts. Firstly, we use cross-country micro data to test the hypothesis that development is negatively related to male 'preference for discrimination'. We show that men's views converge to those of women over the development process and that, for low levels of income, a large majority of men have discriminatory views. Our conclusion is that a turning point occurs at an annual per capita GDP of around 15000. Secondly, we exploit the National Longitudinal Survey of Youth 1979 to find out what cause individuals to change their discriminatory preferences over time.
Keywords: D13; J7; J13; J16; O15; 330; Economic Development; Fertility; Female Labor Force Participation; Gender Discrimination